#BlackCharactersMatter: If I’m Trying to Teach for Social Justice, Why Do All the Black Men and Boys on my Syllabus Die? - Avery, Andrea Serine (Radical Teacher, 2020)
In this essay combining first-person narrative and scholarly literature, a classroom teacher examines the ways in which, despite having a self-professed goal of teaching for social justice, her syllabus centers, upholds, and normalize default whiteness in her classoom. She interrogates her own teaching practice and invites other teachers to do so, as well.